Assessing the Ramifications of the Indo-US Nuclear Agreement on Pakistan’s Regional Standing - Hanif, Erum; Muzaffar, Muhammad (Annals of Human and Social Sciences, 2024)
The study explores the Indo-US Civil Nuclear Deal and evaluates its multiple ramifications for Pakistan. The study peeps into the rationale behind forming the strategic partnership between India and the United States, primarily underlining geopolitical, economic and security motivations that has matured nuclear agreement of 2008. This paper unpacks the concerns of Pakistan, focusing on how the deal may threaten regional stability, the way it treats countries in its nuclear policy and the power shifts in South Asia. This study is qualitative in nature with semi structured interviews from Members of parliament and academicians who contributed their viewpoint on this issue. A self -developed semi- structured interview protocol is used to conduct this study. The interview protocol was developed by the researcher. Purposive and Convenient sampling technique was used to collect data from the targeted population,07 respondents has been interviewed in order to finalize the analysis. Thematic analysis was applied to analyze the data to find recurring points and narratives connected to the nuclear deal and its significance. According to the findings, stakeholders see the Indo-US Civil Nuclear Deal as a factor that has shaken the strategic equilibrium in South Asia, given India a prominent position globally and minimizing Pakistan in terms of its influence. The study brings attention to issues in Pakistan’s capacity related to handling of international affairs and its policy approach. The research concludes by suggesting that foreign policy in Pakistan should be reassessed, strategic communication strengthened and more resources put towards improving diplomatic alliances and nuclear transparency systems.